Effects of temperature and strain rate on tensile stress–strain and workhardening behaviour of P92 ferritic steel. (July 2014) - Sainath, G.; Choudhary, B. K.; Christopher, J.; Isaac Samuel, E.; Mathew, M. D.
Abstract : Detailed analysis on true stress σ –true plastic strain ϵ data indicated that the tensile flow and workhardening behaviour of P92 ferritic steel can be described most accurately by the combination of Ludwigson and Hollomon relations at strain rates ranging from 3·16×10 −5 to 1·26×10 −3 s −1 over the temperature range of 300–923 K. At room and intermediate temperatures, the Ludwigson equation follows the σ – ϵ data closely, whereas at high temperatures, the Ludwigson equation reduces to the Hollomon relation. The variations in σ – ϵ, workhardening parameters and θ – σ with temperature exhibited three distinct temperature regimes. At intermediate temperatures, anomalous variations in σ – ϵ, workhardening parameters and θ – σ with respect to temperature and strain rate have been observed. At high temperatures, the dominance of recovery is reflected in the rapid decrease in flow stress and workhardening parameters associated with Ludwigson/Hollomon relations with increasing temperature and decreasing strain rate.